Evidence for two distinct defect related luminescence features in monolayer MoS2 - Saigal, Nihit; Ghosh, Sandip (Applied physics letters, 2016)
Apart from the defect related emission peak which lies ∼100 meV below the A exciton/trion peak and is labeled D 1 here, this study shows that there is another distinct feature D 2 lying ∼200 meV below A in the photoluminescence spectrum of the exfoliated monolayer MoS2 on SiO2/Si substrates. The D 2 feature is explicitly resolved at low temperature only in few samples. Both D 1 and D 2 do not show circular polarization anisotropy for 633 nm excitation. Both decay with the increase in temperature in a seemingly activated manner with similar activation energy of ∼50 meV, but D 1 decays earlier and therefore D 2 dominates at high temperature in all samples. Annealing in vacuum increases both D 1 and D 2 emission intensities while annealing under sulfur vapour decreases them. Comparison with reported theoretical studies on defects in monolayer MoS2 suggests that these two emissions possibly involve excitons bound to single and double sulphur vacancies, the latter binding excitons more strongly.